Gerakan Filantropi Jaringan Gusdurian ditengah Wabah Covid-19: PHILANTROPHY MOVEMENT OF THE GUSDURIAN NETWORK AMONG THE COVID-19 PLAGUE - Siswoyo Aris Munandar Munandar (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
In the midst of the current Covid-19 outbreak, the Indonesian people are feeling the impact, especially economic problems, as well as many employees who are being sent home. While many people cannot work, it is also difficult to find food, because of that the Gusdurian Network has created a philanthropic movement which is suitable for this research, what form of philanthropy does the Gusdurian Network do? Then what is the background of the Gusdurian Network to enter the philanthropic and social fields? In answering this, the researcher uses field research methodology, namely by calling field data and observing directly. This method the writer will describe the social life of the community as an object of study and dissect the elements in society, the essence of an activity, and the relationship between religious and social aspects. This method will reveal the role of the Gusdurian Movement in philanthropy. Sources of data used are data sources obtained from interviews, observations, and documentation, while secondary data sources are books, journals, and materials that provide guidance on primary sources. The analysis used in this research is inductive analysis. This study aims to see how the tarekat's role in social and philanthropic activities. One of the answers was that Gusdurian made a movement, one of which was Gusdurian Peduli as a form of philanthropy, which began to actively raise funds and set up posts in several cities to distribute aid to those in need. The philanthropic targets of the Gusdurian Network are marginalized groups affected by Covid-19 and poor people. One of the fundraising and aid distribution movements initiated by Alissa Wahid (Chairman / Caregivers of the Gusdur-ian Network) through Gusdurian Cares with Haidar Bagir (through the Love Islam Movement), Kitabisa.com and the #SalingJaga Movement.